The Relationship Between Advanced Lung Cancer Inflammation Index and Adverse Clinical Outcomes in Patients with Myocardial Infarction with No-Obstructive Coronary Arteries - Zhao HW; Wang CF (Journal of Inflammation Research, 2025)
Hong-wei Zhao,1 Cheng-fu Wang2 1Department of Cardiology, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, People’s Republic of China; 2Department of Cardiology, The People’s Hospital of Liaoning Province, Shenyang, People’s Republic of ChinaCorrespondence: Hong-wei Zhao, Email zhaohongwei@sysush.comBackground: The advanced lung cancer inflammation index (ALI) has been suggested as a reliable prognostic indicator for cardiovascular disease. However, the association between ALI and the prognosis of patients with myocardial infarction with no-obstructive coronary arteries (MINOCA) remains undetermined.Methods: In the present study, we consecutively included 437 MINOCA patients. All the patients received a follow-up at 1 week, 1, 3, 6, and 12 months and annually after discharge. The major adverse cardiovascular and cerebrovascular events (MACCE) defined as a composite of all-cause mortality, coronary revascularization, non-fatal stroke, AMI, heart failure or readmission for angina pectoris were recorded. The predictors for MACCE were explored. The ROC analysis was used to determine the predictive value of ALI for MACCE in MINOCA patients.Results: Patients with MACCE had a decreased level of body mass index, albumin and ALI, while an increased level of white blood cell count, neutrophils count, N-terminal proB-type natriuretic peptide, neutrophil-to-lymphocyte ratio, peak cardiac troponin I (P< 0.05). When the patients were divided into three groups according the tertiles of ALI, we discovered that patients with a lower level of ALI tended to suffer an increased risk of readmission for angina pectoris and accumulative MACCE (p< 0.05). The multivariate Cox hazard proportional model showed that a higher NT-proBNP (HR: 1.014, 95% CI: 1.004– 1.023, P=0.005) and a lower ALI (HR: 0.997, 95% CI: 0.995– 0.998, P< 0.001) were independent predictors for MACCE in MINOCA patients (p< 0.05). When ALI≤ 256.97, the specificity was 0.659 and the sensitivity 0.629 (AUC, 0.662; 95% CI, 0.611– 0.714, P=0.026).Conclusion: A lower ALI was an independent predictor for MACCE in MINOCA patients. As a quite easily calculated indicator in clinical practice, ALI can be used in risk stratification and prognostic assessment in MINOCA patients.Keywords: advanced lung cancer inflammation index, myocardial infarction with no-obstructive coronary arteries, predictor, major adverse cardiovascular and cerebrovascular events